Beispiel Nr: 07
$ \text{Gegeben: } \\ P: y=a_1x^{2}+b_1x+c_1 \qquad g:y=mx+t\\ \text{Gesucht:Schnittpunkte zwischen Parabel und Gerade} \\ \text{Parabel-Gerade}\\ \textbf{Gegeben:} \\ p: y==-\frac{1}{2}x^2+4x+6 \qquad g: y==-2x-8 \\ \\ \textbf{Rechnung:} \\f\left(x\right)=-\frac{1}{2}x^2+4x+6\qquad g\left(x\right)=-2x-8\\ \bullet \text{Schnittpunkte zwischen zwei Funktionen} \\ f\left(x\right)=g\left(x\right) \\-\frac{1}{2}x^2+4x+6=-2x-8 \\ -\frac{1}{2}x^2+4x+6-(-2x-8)=0\\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ -\frac{1}{2}x^{2}+6x+14 =0 \\ x_{1/2}=\displaystyle\frac{-6 \pm\sqrt{6^{2}-4\cdot \left(-\frac{1}{2}\right) \cdot 14}}{2\cdot\left(-\frac{1}{2}\right)} \\ x_{1/2}=\displaystyle \frac{-6 \pm\sqrt{64}}{-1} \\ x_{1/2}=\displaystyle \frac{-6 \pm8}{-1} \\ x_{1}=\displaystyle \frac{-6 +8}{-1} \qquad x_{2}=\displaystyle \frac{-6 -8}{-1} \\ x_{1}=-2 \qquad x_{2}=14 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ -\frac{1}{2}x^{2}+6x+14 =0 \qquad /:-\frac{1}{2} \\ x^{2}-12x-28 =0 \\ x_{1/2}=\displaystyle -\frac{-12}{2}\pm\sqrt{\left(\frac{\left(-12\right)}{2}\right)^2- \left(-28\right)} \\ x_{1/2}=\displaystyle 6\pm\sqrt{64} \\ x_{1/2}=\displaystyle 6\pm8 \\ x_{1}=14 \qquad x_{2}=-2 \end{array}\\ \end{array}\\ \\ \text{Schnittpunkt }1\\ f(-2)=-4\\ S(-2/-4)\\\\ \text{Schnittpunkt }2\\ f(14)=-36\\ S(14/-36)\\$